Organized pagan cult in Kievan Rus' - Zaroff, Roman (Studia mythologica Slavica, 1999)
The article attempts to address a common notion in the English speaking world that the pre-Christian Slavic religion was basically animistic. And that personified and anthropomorphic Slavonic deities, known from medieval sources, were a foreign invention. In particular this article focuses on the pagan Kievan cult of the late 10th century as institutionalized by Vladimir the Great. As the Eastern Slavic religion did not evolve in a vacuum, the article analyses it within the broader Slavic and Indo-European context.
Keywords: religija; religion; mitologija; mythology; poganstvo; slovanska mitologija; Slavs; Slovani; božanstva; kulti